The changes in peripheral blood Th17 and Treg ratios in Hashimoto’s thyroiditis are accompanied by differential PD-1/PD-L1 expression - Jun Fang; Lei Yu; Lan-Gen Zhuang; Xiao-Yan Pei; Qiong Wang; Guo-Xi Jin (Frontiers in Endocrinology, 2022)
ObjectiveThe aim of this study was to analyze the percentages of T helper 17 cells (Th17s) and T regulatory cells (Tregs) in autoimmune Hashimoto’s thyroiditis (HT), and the expression of the checkpoint molecules programmed death receptor 1/programmed death ligand 1 (PD-1/PD-L1) on these cells.MethodsThis is a case-control study involving 53 initially diagnosed HT patients (HT group) and 21 normal controls (NC group). The peripheral blood mononuclear cells from the individuals of the two groups were isolated and restimulated ex vivo; the percentage of Th17s, Tregs, PD-1+ Th17s, PD-L1+ Th17s, PD-1+ Tregs, and PD-L1+ Tregs was assessed by flow cytometric analysis.Results(1) The percentage of Th17s in the peripheral blood of the HT group was significantly higher than that of the NC group [(6.38 ± 1.32)% versus (3.12 ± 0.66)%; t = 14.110, P < 0.001], while the percentage of peripheral blood Tregs was significantly lower [(3.82 ± 1.48)% versus (5.61 ± 1.60)%; t = −4.599, P < 0.001]. (2) HT patients’ Th17s expressed PD-1 at a significantly lower frequency than their counterparts in the NC [(6.46 ± 2.77)% versus (18.51 ± 3.96)%; t = −14.842, P < 0.001], while no difference was observed for PD-L1 between the two groups. (3) In contrast, both PD-1 and PD-L1 were expressed at significantly higher frequency on HT patients’ Tregs than on NC [respectively: (17.01 ± 3.04)% versus (10.23 ± 2.77)%; t = 8.850, P < 0.001 for PD-1; (16.60 ± 9.58)% versus (11.36 ± 10.14)%; t = 2.089, P < 0.005, for PD-L1].Conclusion(1) The increased percentage of Th17s and decreased percentage of PD-1+ Th17s in the HT group suggest that a loss of control on Th17 activity through the checkpoint inhibitory axis PD-1/PD-L1 may participate in disease pathogenesis. (2) While the decreased percentage of Tregs in HT patients may explain a lack of regulatory functions able to prevent the autoimmune destruction of the thyroid, the significance of the increased frequency of Tregs expressing PD-1 and PD-L1, previously reported to boost Tregs differentiation, remains to be established. Elucidating this apparent contradiction may reveal important mechanisms underlying HT pathogenesis.